Composition and structure of the culturable gut bacterial communities in Anopheles albimanus from Colombia (2019)
ABSTRACT : The understanding of factors affecting the gut bacterial communities in malaria vectors is essential for the design of vector control interventions, such as those based on a paratransgenic approach. One of the requirements of this method is the availability of bacteria from the mosquito susceptible to culture. Thus, the aim of this study was to evaluate the composition and structure of the culturable gut bacterial communities in field mosquitoes Anopheles albimanus from Colombia, in addition to generate a bacterial collection to further analyze microbial functional activity. Gut bacteria were isolated from An. albimanus larvae and adult mosquitoes collected in localities of the Atlantic and Pacific Coasts. The bacterial isolates were grouped in 28 morphospecies that corresponded to three phyla, three classes, nine families and 14 genera. The larvae guts from San Antero (Atlantic Coast) and Buenaventura (Pacific Coast) shared the genera Bacillus and Lysinibacillus and in adults, Bacillus and Bacillus cereus Group were registered in both localities. Gut bacterial richness was higher in adults from the Pacific with respect to the Atlantic Coast, while larval richness was similar in samples of both coasts. The Shannon index indicated uniformity in morphospecies abundances in both localities. Finally, the characterization of morphospecies from the gut of Anopheles albimanus mosquitoes from Colombia by culture-dependent methods complemented with 16S rRNA gene sequencing allowed the definition, at a finer resolution, of the composition and structure of these microbial communities. In addition, the obtained bacterial culture collection will allow further evaluation of the microorganisms for their potential as biocontrol agents.